AHP-ENHANCED SWOT MATRIX TEACHING STRATEGY - Chipoco, Mario (2016)
The SWOT matrix is the quintessential analysis tool for business purposes, and is taught both in undergraduate and postgraduate courses. However, it is widely understood that the selection of the critical success factors (CSFs) that are included for analysis in the matrix is a very subjective and unstructured process, leaving room for bias and arbitrariness. One way to give a better foundation and support to the analysis results is by utilizing Analytic Hierarchical Process (AHP) in order to weigh the importance of CSFs in the SWOT matrix and increase reliability of the output. This paper contains the design of a strategy to teach this topic in a marketing planning course, with the addition of a useful technique to overcome the limitations of the tool.